Intentions, efficacy, and norms: The impact of different self-regulatory cues on reducing engine idling at long wait stops. (December 2019) - Mahmood, Lynsey; Abrams, Dominic; Meleady, Rose; Hopthrow, Tim; Lalot, Fanny; Swift, Hannah; Van de Vyver, Julie
Abstract: Idling engines contribute significantly to air pollution and health problems. In a field study at a busy railway crossing we used the Theory of Planned Behavior to design persuasive messages to convince car drivers ( N  = 442) to turn off their engines during long wait stops. We compared the effects of three different messages (focusing on outcome efficacy, normative reputation, or reflection on one's intentions) against a baseline condition. With differing effectiveness, all three messages had a positive effect compared with the baseline. Drivers were most likely to turn off their engines when the message focused on outcome efficacy (49%) or reflection (43%), as compared to the baseline (29%). The increased compliance in the normative reputation condition (38%) was not significantly different from baseline. Thus, stimulating self-regulatory processes, particularly outcome efficacy, is demonstrated to have a positive effect on pro-environmental driving behavior. Theoretical and practical implications are discussed. Highlights: Observed driver behavior whilst waiting at railway level crossing. Used persuasive messages based on the Theory of Planned Behavior. Reduced car drivers idling from 71% to between 62% and 51%. Self-efficacy and reflection focused messages were more effective than baseline. Self-efficacy focused message was the most effective (66% increased compliance).